PELAKSANAAN MISI KOTA PEKANABARU: PEMBANGUNAN MASYARAKAT MADANI DALAM LINGKUP MASYARAKAT BERBUDAYA MELAYU TAHUN 2019 - Mardianto, Firki; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indicators of civil society as stated by Han Sung-Jun. There is a social movement based on certain cultural values. Therefore, in order to achieve civil society, a view or goal of the new Pekan Baru city government is built in the 2017-2022 period with the vision of the realization of a new week as a civilian smart city. However, Pekanbaru City Government has only implemented Malay culture in government as symbolic, such as wearing Malay clothes as regulated in Perda No.12 / 2001 and only symbolic buildings such as the use of the Salembayung roof. Meanwhile, according to Prof. Dr. Syamsul Nizar M.A said that there are several identities inherent in the Malay community: For the Malay community, Islam is a spirit that provides encouragement and color for all dimensions of adat and community life. Religious symbols are clearly visible in all Malay traditions, Malay is synonymous with hospitality. The Malay community has high self-esteem even though in its absence, Malays always uphold religion, cultural values, friendship and education. The Malay community puts forward deliberation in solving problems.This research looks at how the implementation of the Malay cultural development mission. More substantially, the goal that will be achieved is to find out the failure model of Paul Light Cascade's implementation, regarding policies, resources, structures, leadership and culture. The location of this research was conducted at the Pekanbaru City Culture and Tourism Office. Furthermore, data collection techniques are carried out by interview, documentation and literature study.The results of this study indicate that the Department of Culture and Tourism in implementing its mission seems symbolic because when viewed from the Paul C. Light indicator, the policy dimensions of the Pekanbaru City Disbubpar focus more on cultural preservation, not on the development and development of Malay culture itself. In addition, when viewed from the dimensions of resources, limited human resources and funding also contribute to influence. As well as in the dimension of the chain of command structure, activities are also centered on the realization of the promise of the elected regional head, which also has a negative effect on the leadership dimension which is dominated by the will of the elected mayor and added to the plural cultural dimension that increasingly suppresses the existence of Malay culture. Keywords: implementation, civilization, development, culture, Malay